Effects of Cycling Intensity on Acute Signaling Adaptations to 8-weeks Concurrent Training in Trained Cyclists - Jones, T. W.; Eddens, L.; Kupusarevic, J.; Simoes, D. C. M.; Furber, M. J. W.; Van Someren, K. A.; Howatson, G. (Frontiers in Physiology, 2022)
This study examined whether the intensity of endurance stimuli modifies the adaptation in strength and endurance following concurrent training and whether the acute molecular response to concurrent exercise is affected by training status. Using a parallel group design, trained cyclists were randomized to either resistance exercise followed by moderate intensity continuous training (RES+MICT, n=6), or resistance exercise followed by work matched high intensity interval training (RES+HIIT, n=7), across an 8 wk training programme. A single RES+MICT or RES+HIIT exercise stimulus was completed 1 wk before and within 5 d of completing the training programme, to assess phosphorylation of protein kinases of the mTOR and AMPK signaling pathways. There were no main effects of time or group on the phosphorylation of protein kinases in response to concurrent exercise stimulus pre- and post-training intervention (p>0.05). Main effects of time were observed for all maximal strength exercises; back-squat, split-squat, and calf-raise (p<0.001), with all improving post intervention. A time x group interaction was present for V̇O2peak, with the RES+MICT group displaying a preferential response to that of the RES+HIIT group (p=0.010). No time nor group effects were observed for 5 min time trial performance, power at 2 and 4 mmol·L-1 (p>0.05). Whilst preliminary data due to limited sample size the intensity of endurance activity had no effect on performance outcomes, following concurrent training. Further, the acute molecular response to a concurrent exercise stimulus was comparable before and after the training intervention, suggesting that training status had no effect on the molecular responses assessed.